Long-term outcomes of therapist-guided Internet-delivered cognitive behavior therapy for pediatric obsessive-compulsive disorder - Fabian Lenhard (Nature Portfolio, 2020)
Abstract Cognitive behavior therapy (CBT) is the recommended first-line intervention for children and adolescents with obsessive-compulsive disorder (OCD), but is not broadly accessible. Internet-delivered CBT (ICBT) with minimal therapist support is efficacious and cost-effective, at least in the short term. Whether the therapeutic gains of ICBT for OCD are sustained in the long run is unknown. In this study, 61 adolescents with OCD who participated in a randomized trial of ICBT were followed-up 3 and 12 months after treatment. The proportion of treatment responders and remitters remained stable from post-treatment to 3-month follow-up and increased significantly from 3-month to 12-month follow-up. This study suggests that the gains of ICBT for youth with OCD are not only maintained long-term, but that further improvements continue to occur during follow-up.